Based on the passage, it can be concluded that the author and Broyles-González hold essentially the same attitude toward

kens on March 31, 2020

writing the conclusion

for P: T-most-S P: T---->R can the conclusion be R-some-S?

Create a free account to read and take part in forum discussions.

Already have an account? log in

Skylar on April 4, 2020

@kenken, happy to help!

Yes, R-some-S is a valid conclusion here.

We start with:
P: T-most-S
P: T->R

Next, we can make deductions from the given statements:
P: T-most-S
P: T->R
not R->not T
C: ?

Now, we should look for ways to put the two premises together. We know that we can combine a Some statement and an S->N statement if they share the Sufficient condition and the arrow points away from the quantifier. This is the case here with the reverse of our first premise and our original second premise. We can combine these to make the following chain: S-some-T->R

We can simplify this to get: S-some-R.
Since some statements are reversible, this also tells us: R-some-S.

Does that make sense? Please let us know if you have any other questions!